Prevention in nursing care: a study protocol of a cluster-randomized controlled trial on the effects of physical exercise and environmental interventions on physical activity behavior and physical functioning in nursing home residents (PROGRESS study) - Belkin, Vera; Janssen, Tanja I.; Rudisch, Julian; Wollesen, Bettina; Voelcker-Rehage, Claudia (Frontiers in Aging, 2025)
BackgroundNursing home residents’ health and psychosocial well-being may be influenced by their often-sedentary lifestyles, which arise due to physical barriers like steps, an unwelcoming environment, limited awareness of the importance of physical activity (PA), and a lack of orientation. While exercise interventions are important for maintaining or improving physical and cognitive functions, they may not help increase daily PA behavior. Therefore, the PROGRESS study aims to investigate the short- and long-term effectiveness of tailored and combined physical exercise and environmental interventions for improving PA behavior and physical functioning among nursing home residents.MethodsThe study employs a cluster-randomized controlled crossover design with four intervention groups. Participants will be randomly assigned to one of four groups: a combined exercise and guided environmental intervention (physical activity-promoting culture), an exercise intervention, a guided environmental intervention, or a non-guided environmental intervention. The exercise intervention involves group-based sessions twice a week, while the environmental intervention focuses on implementing PA into daily routines. The guided environmental intervention is equivalent to the non-guided one but provides additional support two to four times weekly. We aim to recruit at least 120 participants from six nursing homes. Each facility will receive two interventions in a 16-week crossover design (36 weeks in total, including weeks for measurements), followed by a 16-week non-guided environmental intervention (follow-up phase). Primary outcomes include steps per day as an indicator of PA behavior, and the Short Physical Performance Battery (SPPB) to assess physical functioning.DiscussionWe hypothesize that the physical activity-promoting culture will yield superior effects than either intervention alone on the primary outcomes. Furthermore, both the guided environmental intervention and the exercise intervention are expected to be more effective than the non-guided environmental intervention. We aim to encourage nursing home residents to actively participate in social life and to derive guidelines for health promotion.Trial registrationThe study is registered at the German Clinical Trial Register (DRKS) under registration number de DRKS00031020 (23.02.2023) and has received ethical approval from the University of Münster, Faculty of Psychology and Sports Science (2022-40-CVR).